A new molecular classification to drive precision treatment strategies in primary Sjögren’s syndrome - Perrine Soret (Nature Portfolio, 2021)
Sjögren’s syndrome, a disease that primarily affects women, is poorly understood. Here, the authors combine data from a large cohort of patients and healthy controls to identify biomarkers that distinguish patient subgroups to improve our understanding of the disease and facilitate drug development.